ANALYZING SELF-ACTUALIZATION OF JONAS CHARACTER IN THE GIVER NOVEL - Rahayuningsih, Herdiana; Sunggingwati, Dyah; Valiantien, Nita Maya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2019)
This study concerns with Self-Actualization in The Giver novel. Aiming to find the character and personality of Jonas through the Self-Actualization described in the novel. The source of data is taken from The Giver novel by Lois Lowry. This study used Self-Actualization theory by Abraham Maslow. The researchers was employed that Jonas has bravery, sensitive feelings, and intelligence. The results of this research showed that self-actualization found in Jonas are: 1) objective perception, (2) general acceptance of nature, others and oneself, (3) spontaneity, simplicity, and naturalness behaving, (4) needs for privacy and independence, (5) autonomous functioning, (6) freshness of appreciation, (7) mystical or “peak” experiences, (8) concern in social interest, (9) interpersonal relations, (10) recognize discrimination between means and ends, good and evil, (11) present creativeness. When Jonas gets the memories from The Giver, then he shows his self-actualization. The memories open up his mind to think, and to realize that the real world is much beautiful with the difference between one and another. Thus, Jonas is a dynamic character. From Jonas self-actualization, he tries to recognize his own self, develop his ability, his personal uniqueness, and to actualize his potentials as a human being that capable of becoming what he wants to achieve.